Characterization of Corona Plasma Ozone Generators and Analysis of Microbubble Ozone Size for Efficient Mass Transfer - Fitryan, Anggyta; Junaidi, Junaidi; Arif Surtono; Eko Yulianto; Eva Sasmita; Muhammad Nur; Ayu Aprilia; Nida Lidya Susanti; Abdurrahman, Ahmad Faruq (Jurnal Multidisiplin Sahombu, 2025)
This study aims to characterize the performance of a corona plasma ozone generator, measure the concentration of ozone produced, and analyze and compare the size of ozone microbubbles from two diffusers (C50 and C80) to evaluate the efficiency of ozone mass transfer. The method used was experimental with equipment including a VOSOCO ozone generator, Ozone Monitor, dimmer, high voltage probe, Kyoritsu ampere clamp, SANWA multimeter, flowmeter, aquarium, Apexel 12.5x macro lens, C50 and C80 diffusers, and an iPhone 11, with Python-based microbubble size analysis software for digital image processing. The results showed that the ozone generator operated at 1200 V with a linear relationship between voltage, current, and power, where the highest ozone concentration was achieved at a flow rate of 0.8 l/min. The C80 diffuser produced smaller and more homogeneous bubbles (average 3.37 µm) compared to the C50 (4.09 µm), increasing the specific surface area by 21.4% for better mass transfer efficiency. The innovation of this research lies in the development of a Python-based analysis system with an effective and affordable digital image processing approach to characterize ozone microbubble size, providing an accurate alternative for analyzing critical parameters for optimizing microbubble-based ozonation systems.